The Awareness and Practice of Essential Oil among Malaysians: Preliminary Findings - Mazlan, Munirah; Diah, Nurazzura Mohamad (School of Social Sciences, USM, 2017)
Essential oil (EO) is a subtle, aromatic and volatile liquid extracted from the plant source by distillation process or mechanical methods. EO is used widely to enhance life quality and treat illnesses. Aromatherapy, the art of using EO for therapeutic practice is believed to promote healing process through relaxation especially among people who suffer from some stress-related disorder. The objective of this paper is to examine the socio-cultural practices of EO among Malaysians. A pilot survey was conducted to identify the socio-cultural practices of EO among Malaysian. 96 responses were recorded from both males and females from different educational and employment status. The researchers use Statistical Package for the Social Sciences (SPSS) to analyse the data. The analysis suggests that 89.6% women use EO compared to men. The application of EO is different according to gender, age, economic standing and employment status. This study found that 72.9% choose EO for relaxation, 44.8% to treat physical ailments/illness and 40.6% to reduce stress. Interestingly, 58% of the users obtained knowledge of EO from friends and peers, while 55% from the social media. Indeed, most of the respondents agree that EO can help them maintain their physical and emotional wellbeing. Our data also shows that EO is also applied for other purposes such as beautifying the skin and strengthening the immune system. In conclusion, this study has provided culturally relevant implications of EO usage among Malaysians. Although the clinical support for the effectiveness of EO is scarce, the application of EO is widely accepted and being practiced among Malaysians particularly to maintain their emotional wellbeing.